Peranan Guru dalam Menerapkan Nilai-Nilai Filsafat Pendidikan Islam di Sekolah : Studi Kasus di MI Al Anshoriyah Kecamatan Srono - Ali Makrus; Khairul Anam; M. Lukman Hakim; Ahmad Husin (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to analyze the strategic role of teachers in internalizing the philosophical values of Islamic education through the learning process of Islamic Religious Education (PAI) in the classroom. The research focus is directed at how Islamic values are systematically instilled in students at MI Al Anshoriyah, Srono District. This study employs a qualitative approach with a case study method. Data were collected through participatory classroom observations during teaching and learning activities, in-depth interviews with PAI teachers, and documentation of instructional tools (Lesson Plans/RPP). The data analysis technique followed an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that PAI teachers at MI Al Anshoriyah perform the roles of mu'allim, muaddib, and murabbi by instilling three primary philosophical values: 1) I'tiqadiyah (faith-based) values through the strengthening of aqidah; 2) Khuluqiyah (ethical) values through the integration of adab in classroom discussions; and 3) Amaliyah (practical) values through direct worship practices during lessons. The internalization process is supported by dialogical methods and exemplary behavior (uswah hasanah), despite challenges such as the heterogeneous religious backgrounds of students at home. This study concludes that the active role of PAI teachers in contextualizing Islamic philosophical values in the classroom is a key factor in shaping students' religious character from an early age.